Dynamic Motion Luggage - Muhamad Sani Buang; Andrew A/L Steaven (Multidisciplinary Applied Research and Innovation, 2021)
The Dynamic Motion Luggage was designed to enhance the travel experience of travellers around the world through the integration of an auto-follow system. The Dynamic Motion Luggage was constructed as a fully automated device that can also be used as a traditional luggage. It aims to eliminate the need to haul luggage during travels and enable users to free up their hands thus giving them more freedom and reduces strains on the wrist. The product is developed based on an auto-follow system using hardware and software circuit built in the luggage. The auto-follow system in the luggage connects with its user`s smartphone using Wi-Fi and it follows the movement of the phone